Large energy density with excellent stability in fine-grained (Bi0.5Na0.5)TiO3-based lead-free ceramics. Issue 14 (November 2019) - Zhou, Xuefan; Qi, He; Yan, Zhongna; Xue, Guoliang; Luo, Hang; Zhang, Dou
Abstract: In this work, fine-grained (0.95- x )(Bi0.5 Na0.5 )TiO3 -0.05BaTiO3 - x Bi(Zn2/3 Nb1/3 )O3 (abbreviated as BNT-BT- x BZN, x = 0∼0.20) lead-free ceramics are successfully prepared, showing a high energy storage performance. The addition of BZN results in decreased grain size, enhanced breakdown strength and stronger relaxor behavior with polar nanoregions. Slimmer P - E loops are thereby achieved, leading to the improvement of energy density and efficiency. As a result, a high W D of ∼2.83 J/cm 3 is achieved under a relatively low electric field of 18 kV/mm in the x = 0.125 ceramic with submicron-sized grains (∼0.4 μm). The W D value is larger than that of x = 0 ceramic by ∼800%. Furthermore, the x = 0.125 ceramic possesses excellent frequency stability and strong fatigue endurance. The BNT-BT- x BZN lead-free ceramics show promising potential for application in high energy density ceramic capacitors.